2005
DOI: 10.1080/01612840590959416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Social Support Intervention on Health Outcomes in Residents of a Domestic Violence Shelter: A Pilot Study

Abstract: This pilot study tested the feasibility and effectiveness of a social support intervention with women (n = 24) while they were in a domestic violence shelter. Health outcomes were examined pre and postintervention using a randomized control design. The intervention group had greater improvement (p = .013) in psychological distress symptoms and greater improvement in perceived availability of social support (p = .016) than the control group. The intervention group showed less health care utilization (p = .032) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
209
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(230 citation statements)
references
References 26 publications
9
209
2
10
Order By: Relevance
“…For some women, the experience of abuse seems to have provoked them to make changes and increase their awareness about their right to be respected as a dignified human being. The results in this study are consistent with previous national and international studies which emphasize the impact of abuse on the life of women and the effects of abuse on their continued adaptation and contribution to society [3,5,7].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For some women, the experience of abuse seems to have provoked them to make changes and increase their awareness about their right to be respected as a dignified human being. The results in this study are consistent with previous national and international studies which emphasize the impact of abuse on the life of women and the effects of abuse on their continued adaptation and contribution to society [3,5,7].…”
Section: Discussionsupporting
confidence: 82%
“…The psychological and social consequences of abuse are multifaceted. The results of this study correspond in general with previous national and international studies showing that abused women suffer a number of mental health and psychosocial problems such as depression, anxiety and lack of social support [3,18]. In the present study more than half of the abused women reported a moderate to severe level of depression, and the majority of them reported having a low level of social support from their family.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…122 This individually randomised controlled trial compared a structured nurse-led social support intervention with unstructured discussion sessions. Both groups continued to receive standard refuge services.…”
Section: Chaptermentioning
confidence: 99%
“…Although specific client factors were not examined in this study, some of these attributes are characteristic of the women typically seeking counseling and shelter services. For example, previous researchers studying samples of women in shelters have suggested that white women in their early 30's, in long-term married or cohabiting relationships, with 1-2 children, who have left their abusive partners at least one previous time are those most commonly seeking services (Clevenger & Roe-Sepowitz, 2009;Constantino, Kim, & Crane, 2005;Lundy & Grossman, 2009;Gordon, Burton, & Porter, 2004;Harding & Helweg-Larsen, 2009;Simmons, Lehmann, & Collier-Tenison, 2008).…”
Section: Purpose Of the Studymentioning
confidence: 99%